2016
DOI: 10.1080/21655979.2016.1227572
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Schizandrin B against damage of UVB irradiated skin cells depend on inhibition of inflammatory pathways

Abstract: Schizandrin B is extracted from Schisandra chinensis (Turcz.) Baill. This study evaluated the photoprotective effect of Schizandrin B on oxidative stress injury of the skin caused by UVBirradiation and the molecular mechanism of the photoprotective effect of Schizandrin B, and we firstly found that Schizandrin B could block Cox-2, IL-6 and IL-18 signal pathway to protect damage of skin cells given by UVB-irradiation. In the research, we found that Schizandrin B can attenuate the UVB-induced toxicity on keratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The authors showed that the COX-2, IL-6, and IL-18 gene expression were gradually reduced with increasing concentration of schisandrin B, after UVB irradiation. Gao et al evaluated the effects of this compound on expression levels of MMP-1 mRNA and on the synthesis of type 1 pro-collagen after UVB exposure in fibroblasts; the results revealed that schisandrin B reduced MMP-1 gene expression and restored the synthesis of pro-collagen in concentration dependent way [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…The authors showed that the COX-2, IL-6, and IL-18 gene expression were gradually reduced with increasing concentration of schisandrin B, after UVB irradiation. Gao et al evaluated the effects of this compound on expression levels of MMP-1 mRNA and on the synthesis of type 1 pro-collagen after UVB exposure in fibroblasts; the results revealed that schisandrin B reduced MMP-1 gene expression and restored the synthesis of pro-collagen in concentration dependent way [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…The expression of MMPs promotes degradation of the ECM, and MMPs also play a role in skin cancer induced by UV radiation [36]. Through cell surface receptors, IL-1β and TNF-α not only promote the transmission of NF-κB signals, but also activate the transcription of activator protein 1-regulated genes by activating the mitogen-activated protein kinase signaling pathway, inducing the expression of MMPs [37]. Upon UVB radiation of the skin, keratinocytes can indirectly cause skin photoaging by causing the secretion of IL-1β and IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, this compound exhibited anti-inflammatory activity in LPS-stimulated RAW 264.7 cells; in particular, it increased glutathione S-transferase activity and decreased glutathione levels, thereby suppressing edema; this indicates that the anti-inflammatory action of schisandrin A is closely associated with its antioxidant effect ( 28 ). Furthermore, several previous studies have reported that lignan-like substances with a structure similar to that of schisandrin A possess anti-inflammatory activities and excellent Nrf2-induction or ROS-scavenging abilities ( 29 34 ); however, the underlying mechanisms associated with the anti-inflammatory and antioxidant activity of schisandrin A have remained to be fully elucidated. Therefore, the present study evaluated the protective effect of schisandrin A and the underlying mechanisms associated with inflammation and oxidative stress in RAW 264.7 macrophages exposed to LPS derived from Escherichia coli ( E. coli ).…”
Section: Introductionmentioning
confidence: 99%